Sea-mark : the metaphorical voyage, Spenser to Milton - Edwards, Philip, 1923- (Liverpool English texts and studies., 1997)
Concentrating on the way voyage metaphors offer illuminating insights into well-known works, this book suggests some radical reinterpretations of works including Othello, Donne's Hymn to God My God in Sickness, and Bacon's essay on Adversity.